AKTIVITAS Lactobacillus plantarum ISOLAT ASI TERHADAP IMUNOGLOBULIN (IgA , IgG)PADA TIKUS WISTAR MODEL SEPSIS - Sri Sinto Dewi; Herlisa Anggraini (Universitas Muhammadiyah Semarang, 2015)
Lactat acid bacteria which act as a probiotic was a bacteria who can survive to low pH (gastric acid) and bile. Indigenous lactat acid bacteria have a potency as a Immunostimulator for Immunoglobulin (IgA,IgG) lactat acid bacteria used in this research were isolated from breastmilk (ASI). The purpose of this studi were to understand the immunostimulan effect in wistar rat after affected by the pathogen bacteria, and to get the Lactobacillus plantarum suplementation from breastmilk isolate with Elisa methode. The result of study showed that Lactobacillus plantarum from breastmilk could increase the immunoglobulin (IgA,IgG) in wistar rat and have a potency as a ImmunostimulanKeyword : Lactobacillus plantarum, Imunoglobulin (IgA,IgG)